Bioethical aspects of the treatment of mental disorders electroshock - Miraval Rojas, Edgar Jesús (2013)
Introduction: In this study we present the results obtained in relation to bioethical aspects of inpatient treatment in Victor Larco Herrera Hospital, declared not criminally responsible and who are refractory to treatment. Objective: Determining bioethical aspects electroshok treatment, and the level of coordination between the judicial and healthcare. Material and methods: The methodology used for this study was based on a review of the medical records of the ward of the Hospital Department Victor Larco Herrera Hospital. Population: 120 rooms common in patients with acute symptoms are declared not criminally responsible 23 patients (representing 38,33%) Results: In rooms for patients with common mental disorders over 28 declared not criminally responsible patients representing 23,3% of additional beds for public patients, occupied population interned measures according to the offenses, was found, on the contrary would to jail would not comply with the principle of beneficence and justice. Patients held criminally responsible, have the highest percentage of Schizophrenic diagnosis and who are refractory to classical anti psychotic medication is necessary electroconvulsive therapy even considering the adverse effects but that are beneficial for a speddy recovery to the principle of non - maleficence is confronted. Also reported Consent is a patients right to access or not a risky treatment, we do in defence of preserving the principle of patient autonomy. Conclusion: This Work allows us to conclude that it meets the bioethical principles electroshok trearment and there are difficulties in coordination of the judiciary and the health field.